Supplementation Impact of Spirulina platensis Ethanol Extract on Inflammatory Homeostasis Modulation of Rat Spleen at Different Ages - Paramita, Reni; Purba, Hastuti Handayani S; Prijanti, Ani Retno; Iswanti, Febriana Catur (Bogor Agricultural University, Indonesia, 2024)
Pro- and anti-inflammatory mediators need to be released in a balanced way to maintain a healthy state as we age. One important regulatory element in the equilibrium of pro- and anti-inflammatory mediators is NF-κB. The purpose of this study was to examine how S. platensis affected the control of inflammatory mediators in young, healthy, emerging adults and adults in rats. In this investigation, 200 mg/kg BW of S. platensis extract was administered to six groups of male Wistar rats, ages 12, 18, and 24 weeks, along with a control group. In both the treatment and control groups, NF-κB p65 protein expression was lower at 24 weeks than it was at 12 and 18 weeks. TNF-α and COX-2 proteins were lower in the treatment group than in the control group. All age groups in the treatment group had higher levels of IL-10 protein than the control group. The quantity of NF-κB p65 was positively correlated with COX-2 and TNF-α. By raising the concentration of NF-κB p65, the ethanolic extract of S. platensis altered a mediator of cellular immunity. A decrease followed this in TNF-α and COX-2 and a rise in IL-10 in the rat spleen at different ages.